POLIISI- JA UPSEERIPROFESSIOIDEN YHTEISTYÖN UUSIA HAASTEITA - Anttonen, Johanna (Tiede ja ase, 2015)
AbstractThe ongoing structural changes in the Police, and in the Finnish Defence Forces, Defence Reform 2011–2015, tell a stark tale about Finland's financial situation and the demands for the further intensification of work. Both authorities have their own statutory duties that must be taken care of. The security industry is getting rapidly privatised and there is an ongoing discussion about the duties that can still be handled by the authorities with present resources and the duties that can be delegated to a possible commercial third party. What about the citizens, are they expected to participate/have any role in the security activities? Will the whole country and all Finnish nationals be protected and safeguarded if the current level of financing either continues or dwindles? The Police is measuring its reaction times, and the statistics revealing the figures is not a pleasant reading from the point of view of the country as a whole. The present security strategies of the Defence and Interior Affairs administration swear by co-operation and participation in the comprehensive security, whether interior or exterior. There are good models of co-operation, but even with the best intentions, there is no mention of the co-operation of the Police and the Finnish Defence Forces in the co-operative patterns of these strategies. The only reference to this is the authorities' duty to help. The aim of this article is thus to develop means for a new form of co-operation within the security sector between the Police and officers, both operating under jurisdiction. The article concentrates on examining two parallel occupational groups i.e. soldiers and police officers at a time when these two agents could combine their strenghts and acknowledge their shared interests in the common targets of activity of the comprehensive security (such as cyber threats, terrorism, crime from abroad). The world is changing, the security industry is changing and so is the operative field of both the police and the officers. This change must be answered to, either now when the transition could possibly still be controlled, or later when it will take place on the terms of the outer operational environment without the decision makers and their trades, and thus most likely be counterproductive from the perspective of these trades. How to avoid the future threat where financing dictates this transformation instead of the quality of the activity like it should be?